The Influence of Community Knowledge Levels on the use of Amoxicillin in X Apotek - Cendekiawan, Khrisna Agung; Wulandari, Hilwiyah Septi (Global Health Science Group, 2022)
Antibiotics are substances produced by bacteria or synthetic which aim to kill or inhibit the growth of other bacteria, and are substances produced by microorganisms which in low concentrations are capable of inhibiting the growth or killing of other microorganisms. The use of antibiotics is a widely used therapy and is commonly used by health workers as first-line therapy, so that its use is widely found in society. The use of antibiotics must be done appropriately because the side effect that arise due to inappropriate use of antibiotics is the resistance of a disease to antibiotics. There are several factors that influence community knowledge regarding the use of antibiotics including education, occupation, age, experience, information, environment, and culture. The purpose of this study was to determine the effect of the community knowledge level about the use of amoxicillin antibiotics.